The Role of Work Motivation in Mediating Human Resource Competence on MSME Performance in Serang City - Salapudin; Ihwan Satria Lesmana (Indonesian Journal of Business Analytics, 2026)
This study analyzes the mediating role of work motivation in the relationship between individual competency and the performance effectiveness of MSMEs in Serang City. This study adopted a quantitative methodology with a purposive sampling technique, targeting business owners with at least one year of experience. Based on comprehensive data analysis, it is evident that improving human resource competency directly drives MSME performance improvement and strengthens work motivation. Furthermore, work motivation acts as a significant mediating variable, indicating that business efficiency depends not only on professional skills but also on a strong work drive. Therefore, sustainable MSME development strategies must integrate skills enrichment with motivational enhancement programs to achieve optimal operational results